1976
DOI: 10.1021/bi00650a006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of oviduct progesterone receptors analyzed by ion exchange filtration and gel electrophoresis

Abstract: Resolution of the multiple forms of steroid receptors in small samples has been improved by two new techniques: preparative ion exchange filtration and electrophoresis in highly cross-linked polyacrylamide gels of varied concentration. These techniques were used in conjunction with protamine precipitation, gel filtration, and density gradient centrifugation to separate five forms of the progesterone receptor of chick oviduct cytosol. These complexes, numbered I to V in order of elution from agarose gel columns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…The molecular weight of the non-aggregated form determined from the stokes radius and the sedimentation coefficient is much lower (80000) indicating a high asymmetry of the receptor molecule V/fo = 1.40). A similar asymmetry has been found for the estrogen receptor from calf uterus [28] and rat uterus [29] as well as for the progesterone receptor from chicken oviduct [15]. The question now arises, why does the binding protein from crude nuclei show neither aggregation nor the higher molecular weight form.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The molecular weight of the non-aggregated form determined from the stokes radius and the sedimentation coefficient is much lower (80000) indicating a high asymmetry of the receptor molecule V/fo = 1.40). A similar asymmetry has been found for the estrogen receptor from calf uterus [28] and rat uterus [29] as well as for the progesterone receptor from chicken oviduct [15]. The question now arises, why does the binding protein from crude nuclei show neither aggregation nor the higher molecular weight form.…”
Section: Discussionsupporting
confidence: 66%
“…The asymmetry of the receptor molecule, however, is lost, indicating the cleavage of an asymmetric portion of the molecule from a globular estrogen-binding entity. These properties of the receptor fragment obtained after trypsination are very similar to those of the hero-receptor', a small form of the progesterone receptor in chicken oviduct obtained by treatment of the receptor with certain divalent cations [15,27]. Treatment of chromatin with trypsin also yields receptor fragments.…”
Section: Discussionmentioning
confidence: 62%
“…These receptors render hormone specificity to the target tissues and interaction with these proteins is a necessary first step for steroids to exert their effects at the nuclear level. Several laboratories have studied the characteristics of cytoplasmic progesterone receptor of the chick oviduct (Sherman et al, 1970(Sherman et al, , 1976Smith et al, 1974;Spelsberg & Cox, 1976;Toft et al, 1977) and our laboratory reported their purification Coty et al, 1979). Experiments in vitro showed that purified progesterone-receptor complexes can influence directly transcription of chick oviduct chromatin.…”
mentioning
confidence: 75%
“…Oviducts were excised from the oestrogenized animals and treated as before (Sherman et al, 1970(Sherman et al, , 1976Smith et al, 1974;Spelsberg & Cox, 1976;Toft et al, 1977). Cytosol was prepared by using a standard buffer containing 20mM-triethanolamine, pH 8.0, 1 mM-EGTA, and 12mM-1-thioglycerol.…”
Section: Preparation Of Crude Receptorfractionmentioning
confidence: 99%
“…More recent findings, nevertheless, have localized a pyridoxal 5'-phosphate binding site to a proteolytic fragment of the receptor (42) which retains the capacity to bind dexamethasone. This receptor fragment has been referred to as the meroreceptor and is defined as the smallest proteolytic fragment of a steroid receptor which retains the capacity to specifically bind steroid (1,38,43). In these studies, rat thymic glucocorticoid mero-receptors were generated by proteolytic cleavage with either trypsin or chymotrypsin.…”
Section: Alteration Of Steroid Receptor Structure By B 6 Vitamersmentioning
confidence: 99%